COMPARISON OF THE AUCTION PROCESS FOR COLLATERAL AT BNI SHARIA AND BNI BRANCH OF PONTIANAK - Eko Bahtiar (Journal of Enterprise and Development (JED), 2021)
The purpose of this research is to reveal: The Mechanism of the Implementation Process of Collateral Auction at Bank BNI Syariah Pontianak Branch and Comparison of he Implementation Process of Collateral Auction at Bank BNI Syariah and Bank BNI Branch of Pontianak. This research uses qualitative research in which data is obtained from PT. BNI Tbk Pontianak Branch, the Pontianak Branch of the BNI Syariah bank and the Pontianak State Wealth and Auction Service Office (KPKNL). Meanwhile, secondary sources are documents and data at PT. BNI Tbk Pontianak Branch, Bank BNI Syariah Pontianak Branch and Pontianak State Wealth and Auction Service Office (KPKNL). Based on the analysis conducted, the researchers concluded that the differences in the auction process at BNI and BNI Syariah banks, in general, have similarities, such as a listing of collateral auctions at the State Wealth and Auction Service Office (KPKNL), announcement 1 (one) time, announcement II (two) in mass media, auctions, the winner with the highest bid price, after the auction is held, the proceeds from the sale of collateralwill be paid to pay off the debt. If the proceeds from the sale of collateral are less than the total debt of the customer, the bank will collect until the debt is paid off, on the other hand, if the sale of collateral is more than the total debt of the customer, the bank is obliged to collect it. return the auction results to the customer, this is done by all banks, both Islamic banks, and banks. conventional. As for what distinguishes between BNI and BNI Syariah banks, there are 2, namely the first process before submitting the auction, namely the BNI Syariah bank there are more warning periods and the persuasion approach period is more widely applied in the BNI Syariah bank, as well as the eggs higher. Second, the process of resistance or lawsuits for the auction, which is when there is a problem between the bank and the debtor orcustomer refusal when there is dissatisfaction with the auction results.